Marine Pollution Mitigation by Waste Oils Recycling Onboard Ships: Technical Feasibility and Need for New Policy and Regulations - Mazzoccoli, Michela; Altosole, Marco; Vigna, Veronica; Bosio, Barbara; Arato, Elisabetta (Frontiers in Marine Science, 2020)
About 80% of the total pollution from ships is caused by operational oil discharges into the sea, often made deliberately and in violation of international rules; the main reasons can be due to cost savings or lack of adequate facilities in ports to receive waste oils. Therefore, reducing waste oil discharges is crucial for a proper protection of the marine environment. In this regard, the paper presents the preliminary feasibility of a particular waste recycling technology, aimed at obtaining marine fuel oil from sludge, through a pyrolysis process to be carried out in a small reactor onboard. The originality of the research consists in the adaptation of pyrolysis to oily waste produced by ships, since this technology is traditionally applied to solid waste and biomass. Furthermore, the plant has to be designed for operation on board the ship, therefore under very different constraints compared to traditional land plants. Although the preliminary lab tests and simulation results in the chemical process are promising enough, there are still some technical criticalities due to the energy optimization of the reactor for an efficient use onboard of the whole system. In addition, the possibility of recycling waste, directly onboard ships, is not yet covered by mandatory regulations, which is why shipowners generally still feel unmotivated to invest in such technologies.